MOLECULAR AND PHENOTYPIC CHARACTERIZATION OF EFFLUX PUMPS AND EFFLUX PUMPS INHIBITOR ON ANTIBIOTIC RESISTANCE OF SALMONELLA TYPHI IN BAGHDAD - Mustafa Faris Husain; Nuha Joseph Kandala (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of the study was investigate the occurrence of multidrug resistance efflux pumps genes in local clinical isolates of Salmonella sp and try to apply efflux inhibitor for phenotypic detection besides their possibly future therapeutic uses to retain the activity of some frequently used antibiotics. Among 114 bacterial specimens obtained from several hospitals in Baghdad city only 67 isolates were diagnosed to Salmonella typhi according to conventional and molecular methods. The disk diffusion (Kirby Bauer) method was adopted to assess the antibiotic susceptibility of S. typhi isolates, and the results revealed variable rates of resistance to various antibiotics. While Gentamicin are the most effective antibiotic in this study since 100% sensitive to it .Cartwheel method used for evaluating the efflux pumps activity by using ethidium bromide in different concentration, the outcomes appeared positive reaction for 42 isolates (62.6%) at 0.25 µg/ml, 25(37.3%) at 0.5 µg/ml , 15(22.3%) at 1 µg/ml , 9(13.4%) at 1.5 µg/ml , 4 (5.9%) at 2 µg/ml, 4(5.9%) at 4µg/ml. Four isolates which characterized highly expression level of efflux pumps activity and high resistant to antibiotic were selected to confirmed the result of cartwheel assay through determining the minimum inhibitory concentration (MIC) level though applied different concentration (500, 250, 125, 62.5, 31.25, 15.62, 7.8, 3.9, and 1.9) µg/ml of fluphenazine decanoate as efflux pump inhibitor (EPIs) and appeared at 15.62 µg/ml of EPIs the positive activity efflux pumps became negative and Etbr appeared fluorescent.